2019
DOI: 10.1016/j.foodchem.2018.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and attempted differentiation of European and extra-European olive oils using stable isotope ratio analysis

Abstract: European law requires a designation of origin for virgin and extra virgin olive oils (at least in terms of EU/non-EU provenance). Stable isotope ratios have been successfully applied to determine the geographical origin of olive oils, but never to distinguish EU and non-EU oils. In this study 2 H/ 1 H, 13 C/ 12 C and 18 O/ 16 O ratios were analysed in bulk olive oils using Isotope Ratio Mass Spectrometry (IRMS) as well as 13 C/ 12 C and 2 H/ 1 H in the four main fatty acids (linoleic, oleic, palmitic and stear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Climatic conditions influence the rate of uptake of metabolites by plants [37,38]. Also, lower temperatures and frequent rainfall can affect the drying process of forages; essentially, reducing sugars, mineral salts, and soluble nitrogenous substances, while increasing fermentation [39]. Rainfall is usually less frequent in the PDO regions in the present study compared with the non-PDO regions, and the higher concentrations of some sugars (maltose, lactose, mannobiose, talopyranose) in milk of PDO origin may have been due to differences in climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic conditions influence the rate of uptake of metabolites by plants [37,38]. Also, lower temperatures and frequent rainfall can affect the drying process of forages; essentially, reducing sugars, mineral salts, and soluble nitrogenous substances, while increasing fermentation [39]. Rainfall is usually less frequent in the PDO regions in the present study compared with the non-PDO regions, and the higher concentrations of some sugars (maltose, lactose, mannobiose, talopyranose) in milk of PDO origin may have been due to differences in climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The climate and soils of a region directly and indirectly impact the biochemical and biophysical properties of food products. For example, the isotopic and elemental composition of milk is closely related to geographical origin and this carries over to the properties of cheese [39]. To have PDO certification, at least 70% of the dry matter of fodder, or 40% of the dry matter of the ration, must come from the PDO region.…”
Section: Discussionmentioning
confidence: 99%
“…This costly technique has been widely used in the field of food production, and also the number of papers on pharmaceutically relevant herbal drugs has increased. Olive oils from Europe and extra-Europe have been characterized (Bontempo et al 2019), the geographical origin of imported and domestic Camellia sinensis within Turkey (Cengiz et al 2017), and the origin of Panax ginseng samples cultivated in Korea (Chung et al 2018) are reported, and the use of isotopic fingerprint in combination with metabolomics to authenticate Serenoa repens extracts were published recently (Perini et al 2018). However, preciseness and accuracy of results are critically discussed in literature, as terminology employed by different authors is often not clear.…”
Section: Isotope Fingerprintingmentioning
confidence: 99%
“…Consequently, these approaches involve extensive laboratory work, which is usually time‐consuming, destructive, and requires the use of reagents. Although different criteria have been studied for the geographical traceability of virgin olive oil in these studies, the specific criterion of European versus non‐European (EU vs non‐EU) has been scarcely studied and it concerns the European regulation demand . Bontempo et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although different criteria have been studied for the geographical traceability of virgin olive oil in these studies, the specific criterion of European versus non‐European (EU vs non‐EU) has been scarcely studied and it concerns the European regulation demand . Bontempo et al . studied this classification criterion by Isotope Ratio Mass Spectrometry (IRMS) and IRMS coupled with gas chromatography (GC).…”
Section: Introductionmentioning
confidence: 99%